The role of nursing staff in respiratory physiotherapy - Rzepka, Alicja; Kędziora-Kornatowska, Kornelia; Jakubczyk, Marlena; Budnik-Szymoniuk, Maria; Glaza, Izabela; Kusza, Krzysztof (Nursing in the 21st Century, 2011)
Respiratory physiotherapy is an important element of the treatment process. It should be used before as well as after surgery, as 50% of patients’ complications are: pneumonia, deep vein thrombosis and pulmonary embolism. The aim of this study was to asses the role of the nurse in the process of enabling treatment of patients with breathing disorders. We also assessed the possibility of performing exercises in the wards without the help of the physiotherapist. The exercises were divided into expiration deepening, efficient cough and physical therapy.